[Multiple sclerosis]. - Grunwald, I; Kühn, A; Backens, M; Shariat, K; Kostopoulos, P; Papanagiotou, P (2008)
Multiple sclerosis is the most common chronic inflammatory disease of myelin with interspersed lesions in the white matter of the central nervous system. Magnetic resonance imaging (MRI) plays a key role in the diagnosis and monitoring of white matter diseases. This article focuses on key findings in multiple sclerosis as detected by MRI.